2020
DOI: 10.3390/ijerph17072483
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards and Risks Associated with Phthalates among Slovakian Firefighters

Abstract: Despite increasing attention to the occupational risk of firefighters, little is known about phthalate exposure. In our study, we detected mono-isobutyl phthalate (MiBP), mono-n-buthyl phthalate (MnBP), mono(2-ethyl-5-hydroxyhexyl) phthalate (5OH-MEHP), mono(2-ethyl-5-carboxypentyl) phthalate (5cx-MECPP), and mono(2-ethyl-5-oxohexyl) phthalate (5oxo-MEHP) in each urine sample. We detected positive association between MnBP, MiBP, mono-2-ethylhexyl phthalate (MEHP), 5OH-MEHP, 5oxo-MEHP, 5cx-MECPP, mono-isononyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…As expected, we observed temporal trends-declines in concentrations metabolites of phthalates that have been the focus of legislative activities in past. On the other hand, after comparison with our study from 2020 [ 26 ], nowadays we can observe an increase in the median MiNP, which is used as a DEHP substituent. These results correspond well with other findings that observed changes in phthalate exposure in the last decade in the general population.…”
Section: Discussionsupporting
confidence: 58%
“…As expected, we observed temporal trends-declines in concentrations metabolites of phthalates that have been the focus of legislative activities in past. On the other hand, after comparison with our study from 2020 [ 26 ], nowadays we can observe an increase in the median MiNP, which is used as a DEHP substituent. These results correspond well with other findings that observed changes in phthalate exposure in the last decade in the general population.…”
Section: Discussionsupporting
confidence: 58%
“…Professor Jana Duchovicova is an expert in education sciences and teacher training, and is developing cooperation with Kazan Federal University [33]. UKF also has long-term cooperation with Spanish scientists; joint studies have been published, for example, on Danish philosopher S. Kierkegaard and his work [34], refugees' acquisition of L2 [35], and on topics related to natural sciences [36][37][38]. The cooperation between UFK and Spanish Kierkegaardian researchers goes back a long way, Specifically, since 2008 (Kierkegaard and Faith, Barcelona: University of Barcelona), more specifically with Dr. José García Martín (University of Granada) and the Kierkegaardian society he presides (Sociedad Hispánica de Amigos de Kierkegaard).…”
Section: Selected Publication Outputs Of Ukf Staff With Foreign Researchersmentioning
confidence: 99%
“…Food packaging migration has been shown to occur in many different packaging materials such as recycled cardboard packaging, milk bottles, canned food, and water bottles . Related studies include the migration of diisononyl orthophthalate (DINP) from paper packaging materials made of recycled carbonless copy paper to foods, the migration of DBP, BBP, and DEHP from aluminum foil laminates to butter, the transmission of PAEs from polyethylene terephthalate (PET) bottles stored at high temperatures for 10 weeks to water, the migration of PAEs from plastic packaging to sea salts and curries, the migration of PAEs from cans to vegetables and fruits, and the migration of DEHP from plasticized caps or cap seals of glass packages to foods Moreover, numerous studies have shown higher concentrations of PAE metabolites in the urine of individuals who regularly consume plastic packaged foods. ,, Consumers usually perceive paper and board as safe and healthy because of their natural wood origin. However, chemical hazards from potential migrants, such as labels and printing, must also be considered .…”
Section: Fate Of Paes In Different Cooking Processesmentioning
confidence: 99%